Polyphenol analysis using high-resolution mass spectrometry allows differentiation of drought tolerant peanut genotypes - Juliano, Fernanda F; Alvarenga, José Fernando R [UNESP]; Lamuela-Raventos, Rosa Maria; Massarioli, Adna P; Lima, Liziane M; Santos, Roseane C; Alencar, Severino M (Wiley, 2020)
BACKGROUND: Peanut (Arachis hypogaea L.) is an important economic food crop highly appreciated worldwide. Although peanut cultivation has been expanding to dry regions, with water stress during growth stages, current genotypes are not adapted to drought. This study aimed to identify and quantify the full range of polyphenols in five peanut genotypes with different degrees of drought tolerance developed by Embrapa (Brazil) using ultra-high-definition accurate-mass liquid chromatography–electrospray ionization–LTQ-Orbitrap–mass spectrometry. RESULTS: Fifty-eight polyphenols of the classes hydroxybenzoic acids, hydroxycinnamic acids, flavanols, flavonols and flavanones were identified and quantified using high mass accuracy data and confirmed by tandem mass spectrometric experiments. High-definition mass spectrometric analyses revealed nine phenolic compounds that have never been reported in peanuts before. Polyphenol assessment using multivariate analysis allowed identification of the level of similarities among the five peanut genotypes studied. CONCLUSION: Higher drought-tolerant genotypes exhibited higher content of flavonoids, which suggests a relationship between these compounds and drought tolerance traits. © 2019 Society of Chemical Industry.
Keywords: Arachis hypogaea L.; LC-MS/MS; multivariate analysis; phenolic compounds